2003
DOI: 10.1074/jbc.m304282200
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Matriptase Requires Its Noncatalytic Domains, Serine Protease Domain, and Its Cognate Inhibitor

Abstract: The activation of matriptase requires proteolytic cleavage at a canonical activation motif that converts the enzyme from a one-chain zymogen to an active, twochain protease. In this study, matriptase bearing a mutation in its catalytic triad was unable to undergo this activational cleavage, suggesting that the activating cleavage occurs via a transactivation mechanism where interaction between matriptase zymogen molecules leads to activation of the protease. Using additional point and deletion mutants, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
252
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(271 citation statements)
references
References 27 publications
16
252
0
3
Order By: Relevance
“…6 -9 Recent studies suggested that HAI-1/ SPINT1 is responsible not only for the inhibition of matriptase activity but also for the proper intracellular trafficking and activation of matriptase in polarized human epithelial cells. [22][23][24][25][26] We hypothesize that the maintenance of adequate matriptase activity at its proper subcellular localization might require HAI-1/SPINT1. The altered immunolocalization pattern of matriptase observed in the disorganized crypt epithelial cells of the HAI-1/SPINT1-deficient colon may support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…6 -9 Recent studies suggested that HAI-1/ SPINT1 is responsible not only for the inhibition of matriptase activity but also for the proper intracellular trafficking and activation of matriptase in polarized human epithelial cells. [22][23][24][25][26] We hypothesize that the maintenance of adequate matriptase activity at its proper subcellular localization might require HAI-1/SPINT1. The altered immunolocalization pattern of matriptase observed in the disorganized crypt epithelial cells of the HAI-1/SPINT1-deficient colon may support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore formally possible that HAI-1 does not act directly on matriptase during development, but rather on other proteases that act either upstream or downstream of matriptase in a matriptase-dependent proteolytic pathway. However, for the following reasons this does not seem likely: First, biochemical studies have shown that HAI-1 binds directly to matriptase with high affinity and efficiently inhibits matriptase proteolytic activity (Oberst et al, 2003b(Oberst et al, , 2005. Second, shed endogenous matriptase has been isolated in a complex with shed endogenous HAI-1 in breast milk, indicating that a direct interaction occurs between matriptase and HAI-1 when co-expressed in vivo (Lin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular-mass standards are indicated on the left of each blot in kDa. The position at which the catalytic domain part of activated matriptase migrates is indicated on the left by an arrowhead lipoprotein receptor class A (LDLRA) domain (designated D349Y HAI-1), the activated matriptase occurred rarely (Oberst et al 2003b). Therefore, the LDLRA domain of HAI-1 was postulated to play an important role in the process of matriptase activation (Oberst et al 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…The position at which the catalytic domain part of activated matriptase migrates is indicated on the left by an arrowhead lipoprotein receptor class A (LDLRA) domain (designated D349Y HAI-1), the activated matriptase occurred rarely (Oberst et al 2003b). Therefore, the LDLRA domain of HAI-1 was postulated to play an important role in the process of matriptase activation (Oberst et al 2003b). In the present study, we found that the level of activated WT-matriptase that occurred in the conditioned medium from HAI58K-co-expressing cells was similar to that from HAI-KD1-co-expressing cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation